DAMPAK PENGEMBANGAN WISATA GUNUNG RATU TERHADAP EKONOMI MASYARAKAT LOKAL DESA SENDANGREJO KECAMATAN NGIMBANG KABUPATEN LAMONGAN - Siti Shoimah; Nawari - (LPPM UNISDA, 2022)
ABSTRACT This research is based on the problem of developing the Gunung Ratu tourist attraction which then has an impact on the economy of the local community in Sendangrejo Village, Ngimbang District, Lamongan Regency. The problem studied is the efforts to develop the Gunung Ratu tourist attraction and the impact of the development on the local community's economy. This research will be quite interesting because the object under study has modern forms of development combined with history and religion that contribute to the development of the Gunung Ratu tourist attraction which has an impact on the economy of the local community. The purpose of the study was to find out how the impact of the Gunung Ratu tourist attraction on the economy of the local community in Sendangrejo Village. The research method used in this research is descriptive qualitative method. The data obtained in this study were sourced from the results of interviews, observations and documentation from parties related to Gunung Ratu tourism. The results of research in the field indicate that the development carried out for the Gunung Ratu tourist attraction is in the form of infrastructure in tourist areas, motorbike paragliding rentals, and horse rentals. With the formation of this development, local community benefit, such as increased income, the emergence of jobs. Community needs are met, control and ownership are still fully held by the community.